A randomised study to evaluate two different skin closure techniques : subcuticular sutures vs. staples : an investigation into patient satisfaction - Kalim, Mahnaz (Stellenbosch : Stellenbosch University, 2012)
Thesis (MMed)--Stellenbosch University, 2012.